PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA MIE GALAK BONDOWOSO - Halim, Abdul; Setianingsih, Wahyu Eko; Reskiputri, Tatit Diansari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This study aims to examine and determine the effect of two variables, namely product quality and service quality on consumer satisfaction. The hypothesis in this study is that product quality and service quality affect customer satisfaction partially. The object of this research is the consumer of Mie Galak Bondowoso which has a total of 110 respondents using purposive sampling. Data collection techniques using observation, questionnaires, and documentation. The analysis used includes the validity test, reliability test, classical assumption test (normality test, multi-core test, heteroscedasticity test), multiple linear regression analysis and hypothesis testing (t test, determinant coefficient). The results of the study prove that product quality and service quality affect consumer satisfaction at Mie Galak Bondowoso.